New Perspectives on the Greek War of Independence
XXII, 357 p. 15 illus., 12 illus. in color.
Keywords: “This richly textured collection contributes both nuance and precision to our understanding of the emergence of Greece as an independent nation-state. The authors offer new and variegated perspectives on the complex and often poorly-understood ideologies, identities, allegiances, and rivalries that shaped the path to nationhood, thereby suggesting why some of these clearly influential aspects have largely disappeared from conventional accounts both in Greece and abroad.” —Michael Herzfeld, Harvard University, USA “Amidst the abundance of the scholarship on the Greek Revolution, this collection stands out, as it brings together new voices and themes combining them with older questions. Scholars interested in the Greek Revolution, its transnational and local dimensions, its commercial and violent aspects, its echo around the world, its poetic expression, and its legacies throughout the last 200 years, will find much that is new and original here.” — Konstantina Zanou, Columbia University, USA This book marks the 200-year anniversary of uprisings in the Ottoman Balkans between February and March 1821, which became known in the West as the beginnings of the Greek War of Independence (1821–32) and led to the formation of the modern Greek state. It explores the war and its impact on societies involved by delving into the myths that surround it, the realities that have often been ignored or suppressed, and its lasting legacies on national identities and histories. It also explores memory and commemoration in Greece, in other countries impacted, and the Greek diaspora. This book offers a fresh perspective on this pivotal event in Greek, Ottoman, Balkan, Mediterranean, European, and world histories. Yianni Cartledge is a PhD candidate at Flinders University, South Australia. His research explores migration from the Aegean islands to the Anglosphere between 1815-1945. His current case studies include the Ikarians of South Australia and Chiots of London. This is his first edited volume. Andrekos Varnava is Professor of Imperial History at Flinders University, South Australia. He has published four monographs and more than 50 peer-reviewed articles/book chapters on the history of the British Empire, specifically in Cyprus, on the Armenian Question, and on British and Australian migration histories. This is his eleventh edited volume. .